Hubungan Status Gizi Dengan Anemia Pada Remaja Putri di MTS Yapin Taraju Kabupaten Tasikmalaya - Anang Sekarningsih; Eka Vicky Yulivantina; Novita Puspita Dewi (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Anemia is a condition where there is a lack of red blood cells or hemoglobin than normal. The prevalence of anemia in adolescent girls in Asia is 191 million, in Indonesia 7.5 million, in West Java 41%, in Tasikmalaya Regency 185 cases, in Taraju District 25 cases, 3 cases from MTs Yapin Taraju. The aim of the research was to determine the relationship between nutritional status and the incidence of anemia in adolescent girls at MTs Yapin Taraju, Tasikmalaya Regency.Methods: Quantitative research design with correlational descriptive, with approach cross sectional. The population of female teenagers in grades VII, VIII, IX who have menstruated at MTS Yapin Taraju, Tasikmalaya Regency is 80 people. Total sampling technique, sample size of 80 people based on inclusion and exclusion criteria. Result: the 80 respondents with poor nutritional status, the majority experienced anemia, 14 people (17.5%), while the majority of respondents with normal nutritional status did not experience anemia, namely 55 people (68.8%). Test results chi square obtained a p value of 0.000, where it is smaller than the α value (0.000 < 0.05) then Ho is rejected and Ha accepted.Conclusion: There is a relationship between nutritional status and the incidence of anemia in adolescent girls at MTs Yapin Taraju, Tasikmalaya Regency.Keyword: Nutritional Status, Adolescence, Anemia